Long -term selection for a quantitative trait in Tribolium castenum.2. Heritability and realized heritability - Gopikrishna, G; Taneja, V K; Pandey, R S (The Indian Journal of Animal Sciences, 2012)
An experiment with the flour beetle Tribolium castaneum was carried out to study the long-term response to selection for pupal weight for 20 generations. Three population sizes (10, 20 and 40 pairs of parents) and 3 proportions selected (10%, 20% and 30%) were considered along with a control for each population size. The experiment was replicated twice. Fullsib heritability estimates for pupa weight did not follow any definite trend with regard to population size or selection intensity. Pooled realized heritability estimates were 0.52 in periodÂ· 1 (1 to 10 generations) and 0.35 in overall period (1 to 20 generations). At the end of the experiment, the selected and one control line were assayed tor the residual genetic variability. There was a reduction of 54 to 66 % in the heritability estimates measured from offspring-parent regression at the end of the experiment, compared to those estimated in the base population.